Affine Intra-prediction for Versatile Video Coding - Adhuran, Jayasingam; Fernando, Anil; Kulupana, Gosala; Blasi, Saverio (2020 28th European Signal Processing Conference (EUSIPCO), 2021)
New algorithms are being investigated in the context of next generation video coding to achieve higher compression efficiency. In particular, intra block copy is well known to accurately predict screen content and artificially generated content where patterns and edges may repeat within the frame. On the other hand, such type of video content is often subject to geometrical transformations such as transitions, rotations, zooms etc, which may not be accurately captured by simply copying neighbouring pixels. A new intra-prediction scheme is presented in this paper whereby blocks of samples from already reconstructed areas are processed by means of an affine-type transformation. This allows more accurate prediction of blocks which improve compression efficiency in a variety of conditions. Experiments in the context of Versatile Video Coding standard show the proposed method can improve intra-coding compression efficiency by 2.01% BD-rates on average, and up to 4.81%, with negligible impact on the decoder complexity.